Pengaruh Electronic Word of Mouth dan Endorsement terhadap Keputusan Pembelian di Tiktok Shop Pada Mahasiswa Universitas Singaperbangsa Karawang - Fitria Muliyani; Cecep Hermana (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
One of the best features of the Tiktok app is TikTok Shop, a social e-commerce platform that allows users to sell and promote goods while they shop. Of course, electronic word-of-mouth and enticement a tactic used to boost a product or brand's sales cannot be divorced from e-commerce. This study used quantitative methods with multiple linear regression research techniques to investigate whether electronic word-of-mouth and Endorsement influences TikTok Shop purchasing decisions. The sample data used in the study consisted of 100 respondents who were Singaperbangsa University Karawang students. Methods for gathering data through the distribution of surveys made with Google Forms. The study's findings demonstrated that, at a large influence value of 34.3%, Electronic Word of Mouth and Endorsement simultaneously had a positive impact on consumers' decisions to make purchases on TikTok Shop.